Prosedur Penataan Arsip di Kantor Perpustakaan dan Dokumentasi Kota Solok - Darmen, Refni; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper discussed about the procedure managing the archive in the Office of Records and Documentation Solok. The purpose of this paper is to describe the procedure managing the archive in the Office of Records and Dokumentsi Solok. The method used for writing this paper uses descriptive method by exposing about an object as it is at a time based on the data analysis can be summarized as follows: 1) Setup Procedure Records in the Office of Archives and Documentation library of Solok according to region or area Gated system employee. Last save made ​​less irregular, 2) the constraints faced in the Office of Library and archives is the lack of documentation of Solok archival facility and its staff lack an educational background in archives and, 3) the efforts made in the procedure of managing the archive office and library archives Solok documentation procedures that adjust the arrangement of archives with the existing theory paraphernalia weeks to complete the procedure and arrangement of archives and archivists added power. Keywords: archive structurin; procedures archives